VARIABLE SAMPLING INTERVAL SYNTHETIC CONTROL CHARTS FOR JOINTLY MONITORING PROCESS MEAN AND STANDARD DEVIATION - Chen, F L; Huang, H J (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
This paper proposes a synthetic control chart for jointly monitoring the shifts in the mean and/or standard deviation of a normally distributed process. The synthetic chart is a combination of the Max chart and the conforming run length (eRL) chart. The Max chart can be treated as a special case of the synthetic chart. The operation, design, and performance of this control chart are described. Comparisons of the average run length (ARL) performance of the synthetic chart, the Max chart and the traditional joint X and S charts indicate that the synthetic chart outperforms the other two charts. The variable sampling interval (VSI) schemes as an enha.ncement to the synthetic chart are discussed to further improve the chart performance. A numerical example is given to illustrate the application of synthetic chart and its VSI scheme.